ChemInform Abstract: Synthesis of 1, 5‐Dideoxy‐1, 5‐iminoribitol C‐Glycosides Through a Nitrone—Olefin Cycloaddition Domino Strategy: Identification of Pharmacological Chaperones of Mutant Human Lysosomal β‐Galactosidase. Issue 44 (4th November 2014) - Siriwardena, Aloysius; Sonawane, Dhiraj P.; Bande, Omprakash P.; Markad, Pramod R.; Yonekawa, Sayuri; Tropak, Michael B.; Ghosh, Sougata; Chopade, Balu A.; Mahuran, Don J.; Dhavale, Dilip D.
Abstract A new method to prepare iminoribitol C‐glycosides such as (IV), (V), and (VI) is reported.